Pastoral Pancasila Era Liquid Society (Sebuah Analisis Mengenai Pendidikan Pancasila sebagai Media Nation’s and Character Building Sarjana Pendidikan Agama Katolik) - Asa Siri, Theodorus (JURNAL PROPHETA, 2021)
The purpose of this study is to awaken, to revive, and to increase the understanding of Catholic religious education scholars the importance of Pancasila in their existence inthe midst of the plurality in Indonesia. The main objectives to be achieved are to knowthe foundation/framework/vision/mission and objectives of Pancasila education; knowingand understanding the values contained in Pancasila; know and apply the pastoral modelof Pancasila; know and understand the pastoral impact of Pancasila for the Church andthe Indonesia as a country.Pancasila education at the Catholic Religious College played a role as a forum forthe design. So, the presence of Pancasila Education courses is not just meeting thecurriculum criteria in a scientific institution but more than that, Pancasila education isseen as a Media for the mental development of students to view Pancasila as the basis fordeveloping Indonesian Dignity for a Catholic religious education scholar. They becameteachers of Catholicism, nationalism and true Pancasila.